Genesis, Current State, and Development Directions of the Poznań Metropolitan Railway Considering Spatial, Demographic, and Technical-Economic Aspects - Adam Pawlik (Przegląd Komunikacyjny)
Abstract: The article presents the operational principles of the Poznań Metropolitan Railway (PMR) system as an alternative to the increasing share of car transport in the Poznań Agglomeration. One of the main reasons for establishing PMR is the issue of suburbanization, which has led to a significant number of Poznań residents relocating to neighboring municipalities, requiring an efficient commute to Poznań. Research findings indicate that the best solution to this problem is the provision of fast and regular rail connections, particularly for daily commutes to work and school. Furthermore, the article highlights that launching PMR is an economically attractive alternative to expanding the road network, which would be necessary if current transport trends continue.